Designing and validating a health promotion program for women with endometriosis: a mixed-methods study protocol - Mollazadeh, Sanaz; Khadivzadeh, Talat; Mirzaii Najmabadi, Khadijeh; Mirghafourvand, Mojgan; Moradi, Maryam; Moghri, Javad; Hafizi, Leili (Frontiers in Reproductive Health, 2025)
BackgroundEndometriosis is a benign and chronic gynecological estrogen-dependent disease. Research has shown that endometriosis can affect various dimensions of women's lives. It is recommended that programs be developed to improve the quality of life and promote the health of affected women. However, no existing studies have written programs to achieve these goals. Therefore, the present study aims to “design and validate a health promotion program using a logical model”.Methods/designA mixed-methods explanatory design will be used to conduct this study in three phases. The first phase (quantitative phase) is a descriptive-analytical cross-sectional study on 200 reproductive-age women with an endometriosis diagnosis. The Health-Promoting Lifestyle Profile (HPLP-II) and Endometriosis Impact Questionnaire (EIQ) will be used to collect quantitative data. The second phase (qualitative phase) will explain women’s perceptions and experiences of the health-promoting lifestyle. In this phase, the conventional content analysis approach will be used to analyze the data. In the third phase (design of the health promotion program), findings of the quantitative and qualitative phases, the literature review, and focus group discussion (FGD) with a panel of experts will be used to develop a health promotion program based on a logical model, and its validation will be conducted using the Delphi method.DiscussionThis is the first study to use a mixed-methods approach for designing a health promotion program for women with endometriosis. This study can reveal hidden issues in the attitude of patients, medical staff, and those involved in providing health services and provide a better understanding of the factors related to improving the health and quality of life of affected women. In addition, the results of research can be effective in formulating a suitable strategy that can be used by policymakers, planners, and health staff as well as respond to the needs of affected women.